The Analysis of Tempo Media Criticism of the Two Periods of Jokowi's Government (2014-2024): Nawadosa Jokowi Magazine: Analysis of Tempo Media Criticism of the Two Periods of Jokowi's Government (2014-2024): Nawadosa Jokowi Magazine - Tia Nur Aisyah; Alifah Jasmine Kallista Remanu; Kayla Salsabilla Farroza; Amalia Pratiwi; Fatkhuri (ARRUS Journal of Social Sciences and Humanities, 2024)
This study aims to analyze the role of Tempo media in critiquing Joko Widodo's government during two terms (2014-2019 and 2019-2024), focusing on the construction of criticism against government policies. The research employs a qualitative method with a literature study approach and interviews. Data collection techniques involve analyzing articles, journals, and official sources from Tempo. The findings indicate that Tempo employs various consistent and structured criticism patterns, with framing that highlights key issues from the "18 major sins" of the Jokowi administration. The discussion reveals that Tempo's reporting serves not only as criticism but also as a tool to influence public opinion and maintain media independence amidst rapidly changing political dynamics. The conclusion of this study emphasizes that Tempo media plays a significant role in shaping critical narratives against the government and contributes to public discourse in Indonesia.